(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents the scientific conclusions about the activities of the judge and the scientific heritage of Ahmad Donish, who worked in various positions in the Emirate of Bukhara in the second half of the 19th century and created a significant scientific heritage as a result of his active work.The author emphasized that the work of the judge as a defender of Sharia law remained unnoticed by researchers, and scientifically analyzed the views of the great educator on the court of the Bukhara Emirate and his views on Islamic law